Development of gradient microstructure in the lattice structure of AlSi10Mg alloy fabricated by selective laser melting. (1st January 2020) - Liu, Mulin; Takata, Naoki; Suzuki, Asuka; Kobashi, Makoto
Abstract: To identify the microstructural features of the lattice structures of Al alloys built via the selective laser melting (SLM) process, AlSi10Mg alloy with a body-centered cubic (BCC)-type lattice structure was prepared. Characteristic microstructures comprising melt pools with several columnar α-Al phases with <001 > orientations along the elongation direction and surrounded by eutectic Si particles were observed at all portions of the built lattice structure. In the node portions of the lattice structure, a gradient microstructure (continuous change in microstructure) was observed. The columnar α-Al phases were observed near the top surface of the node portion, whereas they became coarser and more equiaxed near the bottom surface, resulting in softening localized near the bottom surface. In the strut portions of the lattice structure, the columnar α-Al phases were elongated along the inclined direction of struts. This trend was more prevalent near the bottom surface. The α-Al phases became coarser and more equiaxed near the bottom surface as well. The aforementioned results were the basis of a discussion of the development of the gradient microstructure in lattice-structured Al alloys during the SLM process in terms of thermal conductivities at the boundaries between the manufactured (locally melted and rapidly solidified) portions and adjacent (unmelted) alloy powder.